Rumex chalepensis (Polygonaceae), a new species for Morocco and Africa - Verloove, Filip; Chambouleyron, Mathieu; Léger, Jean-François (Mediterranean Botany, 2022)
The Irano-Turanian Rumex chalepensis has been recorded in two localities in Morocco since 2013, apparently for the first time in Africa and rather disjunct from the species’ known distribution range. Populations were found in eastern Morocco: one close to the city of Midelt (High Moulouya valley), in the high plains between the Middle Atlas and High Atlas mountain ranges, whereas the second is located close to the city of Jerada (Lower Moulouya valley / High plateaus), close to the border with Algeria. This species is morphologically similar to R. obtusifolius and might have been overlooked elsewhere in North Africa. The presence of the latter in Morocco, always assumed to be very questionable up to present, is also confirmed here. Distinguishing features for these two species are discussed, some illustrations are also presented and R. chalepensis is lectotypified. It is most likely a naturalized weed in Morocco although it cannot be completely ruled out that it is a previously overlooked native species with two disjunct areas, an Irano-Turanian and North African one.